SOSIALISASI DAN PENDAMPINGAN HUKUM KEKAYAAN INTELEKTUAL DALAM PENDAFTARAN MEREK DAGANG BAGI PELAKU UMKM DAN NON UMKM DI RPTRA ANGGREK LEBAK BULUS - Dinanti, Dinda; Fadila Rika Farisa, Pawit; Putri Indira, Tirsa; Panji Rahmatullah, Raden; Welgaputri, Feby; Josephine Siregar, Karina (Zhata Institut, 2024)
MSME players play a major role in the pillars of the economy in Indonesia. Reporting from the Indonesian Ministry of Finance, showing the results of data from the Ministry of Cooperatives and SMEs, the number of MSMEs currently reaches 64.2 million with a contribution to GDP of 61.07 percent or worth 8,573.89 trillion rupiah. Unfortunately, there are still many MSME actors who do not know about the benefits and importance of trademark rights. This causes MSME actors not to register their intellectual property rights, even though Trademarks have an important role for producers and consumers. Therefore, we carry out this Community Service Activity at RPTRA Lebak Bulus, with the hope of providing education and understanding to the surrounding community and MSME Actors around RPTRA Lebak Bulus, in the form of understanding the importance of Trademark Rights from an economic perspective, threats and applicable policies. The results of this activity have shown positive results, namely the increase in Participants' understanding of the importance of Trademark Rights Registration from the economic side, threats and applicable policies, based on the data that we have obtained in the implementation of this Community Service activity